2018
DOI: 10.1111/mmi.14089
|View full text |Cite
|
Sign up to set email alerts
|

Functional definition of the two effector binding sites, the oligomerization and DNA binding domains of the Bacillus subtilis LysR‐type transcriptional regulator AlsR

Abstract: The LysR-type transcriptional regulator (LTTR) AlsR from Bacillus subtilis activates the transcription of the alsSD operon encoding enzymes for acetoin formation in response to the presence of acetate. The structural basis for effector binding, oligomerization, DNA binding, higher ordered complex formation, DNA bending and transcriptional control by B. subtilis AlsR was functionally characterized. The binding of two molecules of acetate per molecule AlsR was determined. Acetate-dependent transcription complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…These findings indicated that S100A11 regulates TKT at the transcriptional level. Previous reports demonstrated that the S100A family can act as transcription factors to modulate gene expression [ 18 , 19 ]. S100A11 was found to be strongly expressed in the nucleus in PDAC tissues (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These findings indicated that S100A11 regulates TKT at the transcriptional level. Previous reports demonstrated that the S100A family can act as transcription factors to modulate gene expression [ 18 , 19 ]. S100A11 was found to be strongly expressed in the nucleus in PDAC tissues (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In these cases, additional binding sites are defined in the promoter region, and effector binding to the regulator provokes a conformational change that results in a shift of the DNA binding site, especially from a proximal SBS subsite to a distal SBS subsite, contributing to the relaxation of the DNA bending angle (29)(30)(31). In some other regulators, few changes in promoter binding are observed upon activation, and a mechanism differing from the sliding dimer is proposed (32). An increasing number of LTTR-regulated systems deviating from these architectures and activation mechanisms are being uncovered, so that no common activation mechanism can be proposed (33)(34)(35)(36)(37).…”
mentioning
confidence: 99%
“…Binding of DbdR to P dbhL (A), P orf18 (B) and P orf20 (C) promoter DNA. EMSAs of32 P-labeled promoter DNA fragments with purified extracts containing DbdR protein were performed as described in Materials and Methods with either no protein added (lane 1) or increasing amounts of DbdR-enriched extract (purified extract): (A) 0.8, 1, 1.2, 1.6, 1.8, and 2 g/l; (B) 0.1, 0.2, 0.3, 0.4, and 0.8 g/l (lanes 2 to 6); (C) 0.5, 0.8, 1, 1.2, 1.6, 1.8, and 2 g/l (lanes 2 to 8). An excess of specific unlabeled promoter DNA fragment (lane 8 in panel A, lane 7 in panel B, and lane 9 in panel C) was added to a reaction mixture that also contained the maximum amount of crude extract.…”
mentioning
confidence: 99%
“…To efficiently activate the transcription of corresponding target genes and hence influence cellular processes in bacterial, the binding activity of LTTRs to its target gene is generally influenced by one or more effectors. For example, acetate is the effector of AlsR and activates the transcription of the alsSD operon for acetoin formation in Bacillus subtilis ( 26 , 38 ), glutarate is the effector of GcdR and controls glutarate catabolism in Pseudomonas putida KT2440 ( 29 ), hydroxyhydroquinone or possibly 2,3,5-trihydroxybenzoate is the effector of DbdR and influences expression of the entire 3,5-DHB anaerobic degradation pathway in Thauera aromatica ( 48 ), benzoate and cis,cis-muconate are the effectors of BenM and control aromatic compound degradation in Acinetobacter sp. ADP1 ( 45 ), 1-Naphthol is the effector of McbG to activate mcbBCDEF cluster transcription and involved in the upstream pathway of carbaryl degradation in Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 99%